2020
DOI: 10.1101/2020.06.16.154286
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparing library preparation methods for SARS-CoV-2 multiplex amplicon sequencing on the Illumina MiSeq platform

Abstract: Genomic surveillance has a key role in tracking the ongoing COVID-19 pandemic, but information on how different sequencing library preparation approaches affect the data produced are lacking. We compared three library preparation methods using both tagmentation (Nextera XT and Nextera Flex) and ligation-based (KAPA HyperPrep) approaches on both positive and negative samples to provide insights into any methodological differences between the methods, and validate their use in SARS-CoV-2 amplicon sequencing. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…For samples requiring immediate attention, e.g. those from patients potentially involved in an active outbreak, adapters were added with the DNA Prep kit (Illumina) as previously described 24 . Amplicons were sequenced on the MiSeq platform, using a Nano 500 cycle kit with v2 chemistry (Illumina) (https://doi.org/10.17504/protocols.io.bnnbmdan).…”
Section: Rapid-turnaround Adapter Addition and Sequencingmentioning
confidence: 99%
“…For samples requiring immediate attention, e.g. those from patients potentially involved in an active outbreak, adapters were added with the DNA Prep kit (Illumina) as previously described 24 . Amplicons were sequenced on the MiSeq platform, using a Nano 500 cycle kit with v2 chemistry (Illumina) (https://doi.org/10.17504/protocols.io.bnnbmdan).…”
Section: Rapid-turnaround Adapter Addition and Sequencingmentioning
confidence: 99%
“…The present study does have several limitations. First, the 4 methods were tested on a limited number of European samples, all affiliated to the lineage B1, according to the Pangolin classification (23); the present evaluation should be confirmed in larger studies including other lineages in order to be more representative of the global ecology of this emerging virus.As SARS-CoV-2 sequencing is an expanding market and other methods has been published(24)(25)(26) or are probably under development, the present study is not exhaustive. However, the approaches selected herein are representative of the methods mostly used during pandemics and are easy to implement in a diagnostic laboratory.…”
mentioning
confidence: 99%
“…The ARTIC Illumina method, a tiling multiplex PCR approach, was the first that enabled WGS of SARS-CoV-2 using Illumina sequencers [29] . The technique has subsequently been optimized and analysis, albeit in small sample numbers, concluded that it delivers sufficient quality to perform phylogenetic analysis [30] , [31] , [32] . It had been used as targeted and random RT-PCR screening with subsequent sequencing of the population in order to study the spread of SARS-CoV-2 through the community [24] .…”
Section: Discussionmentioning
confidence: 99%